Factors of Customer Loyalty and Retention in the Digital Environment - Matheus de Sousa Pereira; Beatriz Schmitt de Castro; Brenda Alves Cordeiro; Bruno Schmitt de Castro; Maria Gabriela Mendonça Peixoto; Eugenia Cornils Monteiro da Silva; Marcelo Carneiro Gonçalves (Journal of Theoretical and Applied Electronic Commerce Research)
Customer loyalty and retention are crucial for digital platforms, yet systematic studies integrating technological innovation and loyalty strategies remain scarce. This study addresses this gap by conducting a bibliometric analysis of key factors influencing customer retention in the digital environment. Our research employs a quantitative bibliometric approach using the Biblioshiny and Bibliometrix tools (RStudio 2022.02), analyzing 300 scientific articles from the Web of Science database (2021–2024). This study applies bibliometric techniques such as descriptive metrics, bibliographic coupling, co-citation, and scientific collaboration mapping to identify trends and thematic clusters. Our findings indicate that emerging technologies, including artificial intelligence and big data, significantly impact customer experience, trust, and engagement. Personalization and digital innovation emerge as fundamental drivers of customer retention, offering strategic insights for companies aiming to strengthen competitiveness in the global digital market.